Atypical Presentation of a Tick Paralysis in a Dog - Erdem Gülersoy; İsmail Günal (Acta VETERINARIA Indonesiana, 2022)
An 11-month-old Guregh dog was admitted to the hospital with history of vomiting and regurgitation, gait disorder and unilateral thread-like hypersalivation for last a few days. Clinical and radiographic examinations revealed quadriplegia, facial paralysis, grave MGCS (5) and VAS (4) scores, severe megaesophagus and gas-filled distended intestines. In hematochemical analysis, leucocytosis due to granulocytosis with polycythemia, elevated BUN, creatinine, CPK and AST levels were determined. During careful clinical examination, engorged ticks were found in the head and neck region of the dog. After excluding diseases that may cause similar symptoms, diagnosis of atypical tick paralysis was made on the basis of clinical findings such as history of vomiting and regurgitation before the onset of gait abnormalities and the presence of megaoesophagus although the patient is less than 1 year old. The clinical appearance, MGCS and VAS scores improved after 5 days of hospitalization period. It was concluded that the presence of megaesophagus in young dogs with vomiting and/or regurgitation before the onset of neurological findings are observed in atypical tick paralysis and hospitalization of the patient, tick removal, supportive treatment administration and MGCS and VAS score assessments provide successful clinical results.